1511. Influenza antiviral use in patients hospitalized with laboratory-confirmed influenza in the United States, FluSurv-NET, 2015 – 2019. (31st December 2020) - Tenforde, Mark W; Cummings, Charisse N; Sutton, Melissa; Kim, Sue; Maslar, Amber; Alden, Nisha B; Spina, Nancy; Price, Andrea; Monroe, Maya; Rothrock, Gretchen; McMahon, Melissa; Talbot, Helen; et al.
Abstract: Background: Antiviral therapy is recommended for all patients hospitalized with influenza to reduce morbidity and mortality. We used data from the population-based Influenza Hospitalization Surveillance Network (FluSurv-NET) to evaluate trends in influenza antiviral use in patients hospitalized with influenza over 4 seasons in the United States. Methods: We included cases residing within the FluSurv-NET catchment area and hospitalized with laboratory-confirmed influenza from October 1 – April 30 during 2015-16 through 2018-19 seasons. For 2015-16 and 2016-17, chart abstraction of demographic and clinical characteristics and antiviral use was performed on all cases; for 2017-18 and 2018-19, all patients < 50-years and an age-stratified random sample of older adults were sampled. Data were weighted to reflect the probability of selection. We assessed the frequency of treatment, by season and age group, and evaluated trends by season using the Cochran-Armitage test. Among those receiving antivirals, we used multivariable logistic regression to assess the association between the days from symptom onset to admission and receipt of early (0-2 days from symptom onset) versus late (> 2 days) treatment, adjusting for age, sex, race/ethnicity, and underlying medical conditions. Results: Over 4 seasons, we sampled 62, 182 patients; 54% female and 63% non-Hispanic white. Overall, 92% of patients received antivirals, increasing from 86% in 2015-16 to 94% in 2018-19; use increased by season in all age strata (p < 0.001) [Figure]. Most received oseltamivir (99%); in 2018-19, 2% received baloxavir. Of those who received antivirals, 38% received early treatment. The median days from symptom onset to admission was 1 day (interquartile range [IQR] 1-3) for those who received early treatment and 4 days (IQR 3-6) for those who received late treatment. Ninety-three percent who received antivirals started within 1 day of admission. For each additional day from symptom onset to admission, the adjusted odds of late treatment was 8.56 (95% confidence interval: 7.83-9.35). Figure. Weighted percentage of hospitalized patients receiving influenza antivirals by influenza season and age strata, FluSurv-NET, 2015-16 through 2018-19. Conclusion: In patients hospitalized with influenza, most received antiviral treatment within 1 day of admission. However, a majority had delays from symptoms onset to initiation, due to late presentation of illness. Disclosures: Melissa Sutton, MD, MPH, CDC funding (Emerging Infections Program) (Grant/Research Support) Sue Kim, MPH, Council of State and Territorial Epidemiologists (CSTE) (Grant/Research Support) Nisha B. Alden, MPH, CDC (Grant/Research Support)